APLIKASI ALGORITME BRANCH AND BOUND DALAM MODEL OPTIMISASI ROBUST - RIZKIANA, LAILATUL; TASTRAWATI, NI KETUT TARI; SUCIPTAWATI, NI LUH PUTU (E-Jurnal Matematika; Vol 8 No 4 (2019)DO - 10.24843/MTK.2019.v08.i04.p266, 2019)
Bali is one of the regions in Indonesia which is famous for its tourism. Vacationing in Bali seems to be a must for every tourist, both domestic and foreign tourists. For tourists who are on vacation many things are considered be it time, distance, cost and others. Travel time with a distance that is already known is something that can not be estimated with certainty, given the many factors that influence including traffic conditions, weather, or road infrastructure. Robust optimization is one area of ??optimization that solves problems with uncertainty which in this study uses a box uncertainty set approach. Optimization problems can be solved by a branch and bound algorithm, the results obtained in the form of tourist attraction routes should be chosen with a minimum time and influenced by indefinite factors.